Nrf2 participates in mechanisms for reducing the toxicity and enhancing the antitumour effect of Radix Tripterygium wilfordii to S180-bearing mice by herbal-processing technology - Jun-Ming Wang; Jin-Yang Li; Hong Cai; Rong-Xing Chen; Yue-Yue Zhang; Lu-Lu Zhang; Ying Cui; Yong-Xian Cheng (Taylor & Francis Group, 2019)
Context: Radix Tripterygium wilfordii Hook. f. (Celastraceae) (LGT) has outstanding curative efficacy; however, side effects include high toxicity, particularly hepatotoxicity and nephrotoxicity. Objective: To investigate detoxification mechanisms of LGT through processing separately with each of these medicinal herbs including Flower Lonicera japonica Thunb. (Caprifoliaceae) (JYH), Radix Paeonia lactiflora Pall. (Ranunculaceae) (BS), Herba Lysimachia christinae Hance (Primulaceae) (JQC), Radix et Rhizoma Glycyrrhiza uralensis Fisch. (Fabaceae) (GC) and Seed Phaseolus radiatus L. (Fabaceae) (LD) in S180-bearing mice by involving nuclear factor (erythroid-derived 2)-like 2 (Nrf2). Materials and methods: LGT raw and processed products were orally administered at 60 mg/kg to KM male mice inoculated with S180 tumour cells for 14 consecutive days, and blood, tumour, liver and kidney were taken to observe the detoxifying effects and biological mechanisms. Results: Herbal-processing technology significantly weakened hepatotoxicity and nephrotoxicity evoked by LGT with ED50 of the converted triptolide in each processed-herb product for serum alanine transaminase, aspartate transaminase, creatinine and urea nitrogen of 9.3, 16.6, 2.5 and 4.2 μg/kg, for liver glutathione, glutathione S-transferase, catalase, tumour necrosis factor-α and interleukin-10 of 114.9, 67.8, 134.1, 7.7, 4171.6 μg/kg, and for kidney 21.9, 20.5, 145.0, 529.7, 19.4 μg/kg, respectively. Moreover, herbal-processing technology promoted the accumulation of Nrf2 into the nucleus, and upregulated mRNA expression of Nrf2 and heme oxygenase-1. Additionally, herbal-processing technology enhanced the tumour inhibition rate with ED50 12.2 μg/kg. Discussion and conclusions: Herbal-processing technology improves the safety and effectiveness of LGT in cancer treatment, and future research may be focused on the Nrf2-related molecules.